Examining memory reconsolidation as a mechanism of nitrous oxide’s antidepressant action - Williams, E; Taujanskaite, U; Kamboj, SK; Murphy, SE; Harmer, CJ (Springer Nature [academic journals on nature.com], 2025)
There is an ongoing need to identify novel pharmacological agents for the effective treatment of depression. One emerging candidate, which has demonstrated rapid-acting antidepressant effects in treatment-resistant groups, is nitrous oxide (N2O)—a gas commonly used for sedation and pain management in clinical settings and with a range of pharmacological effects, including antagonism of NMDA glutamate receptors. A growing body of evidence suggests that subanaesthetic doses of N2O (50%) can interfere with the reconsolidation of maladaptive memories in healthy participants and across a range of disorders. Negative biases in memory play a key role in the onset, maintenance, and recurrence of depressive episodes, and the disruption of affective memory reconsolidation is one plausible mechanism through which N2O exerts its therapeutic effects. Understanding N2O’s mechanisms of action may facilitate future treatment development in depression. In this narrative review, we introduce the evidence supporting an antidepressant profile of N2O and evaluate its clinical use compared to other treatments. With a focus on the specific memory processes that are thought to be disrupted in depression, we consider the effects of N2O on memory reconsolidation and propose a memory-based mechanism of N2O antidepressant action.